Legacies of the parallel worlds of Rutherford and Kamerlingh-Onnes, 1908 - Tallon, Jeffery (New Zealand Science Review, 2009)
This paper, on the occasion of the centennial of the award of the Nobel Prize to Rutherford, focuses on the simultaneous, but very different, achievements of Rutherford and Dutch physicist Kamerlingh-Onnes using atomic and bulk helium. One established the field of nuclear physics while the other the field of low-temperature physics and the discovery of superconductivity. The two are now inseparable in modern nuclear physics.